Green science and technology - Park, Enoch Y.; Saito, Takayuki; Kawagishi, Hirokazu, 1958-; Hara, Masako, 1944- (Boca Raton : CRC Press, 2019)
This book provides a comprehensive and up-to-date review of recent trends of green science and technology. Worldwide deterioration of environment and global warming threaten our lifestyle and the survival of all creatures. In order to weather these problems, we need to construct a multidisciplinary approach involving the fusion of various advanced researches. The book begins with an overview on fundamental research about generation and utilization of renewable energy, protection of the earth's ecosystem for better coexistence with nature, development of artificial intelligence-based agriculture and molecular recognitionbased welfare and covers a wide range of innovative research on green science and technology.
OCLC-licensed vendor bibliographic record.
Keywords: NATURE / Environmental Conservation & Protection; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; Green technology; Environmental sciences